Hubungan Dukungan Sosial Keluarga Dengan Prestasi Belajar - Isabella Rahmawati; Bhisma Murti; Nunuk Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Learning achievement is the level of success in learning the subject matter is expressed with a gradeevery field of study after experiencing the learning process. Good family support will assist students in achievingoptimal, besides from the family, motivation can be obtained from the surrounding environmentObjective: To determine the relationship of family support with student learning achievement.Methods: This research is descriptive correlation with cross sectional approach. Population of the research are student level II at DIII Midwifery Academy Of Mamba’ul Ulum Surakarta. The number of samples are 79 students witha total population. Instruments of research on family social support variables using questionnaires, while variablelearning achievement using secondary data. Relationship analysis two variables with chi square analysis.Results: Based on the results obtained by analysis of a significant relationship between social support families withlearning achievement (OR = 3.20; 95% CI 1.14 to 8.93; p = 0.027).Conclusion: There is a relation families social support with Learning achievement.Keywords: Familly Social Support, Learning achievement